Active aging awareness and well-being among older adults in Portugal - Costa, Andreia; Henriques, Joana; Alarcão, Violeta; Henriques, Adriana; Madeira, Teresa; Virgolino, Ana; Sousa, Joana; Feteira-Santos, Rodrigo; Arriaga, Miguel; Rocha, Jorge; Nogueira, Paulo (Frontiers in Public Health, 2023)
Objective: This study aims to assess the active aging awareness of older adults in mainland Portugal and their levels of overall well-being and to identify social and health-related factors. Methods: A cross-sectional study was conducted with a representative sample of 613 older adults, aged 65 or older, who participated in the PROKnos – Knowing Social Prescribing needs of the elderly study in Portugal. The questionnaire consisted of the Active Ageing Awareness Questionnaire and the World Health Organization – Five Well-Being Index, as well as sociodemographic, economic, and health status questions. Correlation coefficients, t-tests for independent samples, and one-way ANOVA were used to explore potential associations between variables. Results: The active aging awareness levels were significantly higher for women (p = .031), and those who were younger (p = .011), more educated (p <.001), had a better financial situation (p <.001), and had better health (p <.001). The same pattern was found for well-being, except in relation to gender, as men had higher levels (p = .016). These variables were found to be correlated. Discussion: Even though active aging is an important strategy to implement, it is indispensable to consider the perceptions and conditions that need to be in place before that. This study reveals that several social and health-related factors are associated with well-being and active aging awareness, as well as the differences between groups that exist in mainland Portugal in relation to that. This emphasizes how vital it is to address social inequalities in active aging efforts, which are not necessarily uncovered when only considering actual active aging measures.